abla-Fredgolm operators in Banach-Kantorovich spaces - Kudaybergenov, K. K. (Methods of Functional Analysis and Topology, 2006)
The paper is devoted to studying abla-Fredholm operators in Banach–Kantorovich spaces over a ring of measurable functions. We show that a bounded linear operator acting in Banach–Kantorovich space is abla-Fredholm if and only if it can be represented as a sum of an invertible operator and a cyclically compact operator.